Radiographic Examination Profile In Pediatric Patients - Felayani, Fadli; Isnoviasih , Susi Tri; Wibowo, Ardi Soesilo; Aryani, Asri Indah (Jurnal EduHealth, 2024)
Several unique things differentiate radiographic examinations in pediatrics from adult patients, including patient fixation, the level of patient cooperation, and the need for patient companions. Currently, no literature provides an overview of the patient's age with these three aspects of radiographic examination. This study aims to provide an overview of the relationship between age groups and the implementation of radiographic examinations, which greatly influence the success of the examination. This research is a type of descriptive observational research. Data obtained from three hospitals was collected for one month. The sample for this study was 144 pediatric radiographic examinations. The study results are described in frequency distributions related to patient fixation, level of patient cooperation, and the need for patient companions. The study results showed that patients began to cooperate, and the use of fixation decreased in the age group of three years and above. Patients begin not needing a companion at six years and above. The radiographer must evaluate these three things to prepare the examination with an appropriate approach with the goal of a successful exam without repetition so that the radiation dose is minimal for both the patient and the patient's family. This research can be used as a guide for radiographers in preparing for examinations and initial communication during pediatric radiography examinations.